Economic crisis impact on changes in international financial institutions operating - Slobodan Cerovic; Pero Petrovic; Stanislav Cerovic (UTMS Journal of Economics, 2013)
The emergence and deepening global economic crisis is in large part reflected in the operation of international financial institutions and their current structure. Long-term financial crisis has increased demands for decisive reform moves in operating and structure of the IMF, World Bank Group and other global and regional financial institutions. This means that so far the results of their policies are inadequate and that their role is subject to critical observation. The crisis has imposed the need to reform international financial institutions and new global financial architecture. Changes in their structure and operation should lead to global economic stability. Members of the Euro zone are faced with a new attitude towards the international financial institutions, particularly the International Monetary Fund. Proclaimed missions of International Monetary Fund and World Bank clearly differ in theory, but with the passage of time their activities have become increasingly intertwined.
Keywords: G01; G2; 330; The Economic crisis; impact changes; structure functioning; financial institutions.